Geographic and reactive routing protocols for MANET - Srivastava A.; Kumar D.; Gupta S.C. (My University, 2025)
Mobile Ad-hoc Network (MANET) is a readily deployable wireless network suitable as a communication backbone during emergency response operations. These networks are infrastructure less. The goal of this paper is to simulate the scenarios for emergency situations. Various routing protocols have been proposed for MANETs like AODV, DSDV, LAR, DYMO, TORA etc. They are classified as proactive (table driven), reactive (on demand), geographic (based on GPS) etc. We have chosen three reactive routing protocols viz. LAR [1], DYMO [2], AODV [3] for performance evaluation. The mobility scenario is generated with random waypoint mobility model. Packet delivery fraction and end to end delay is estimated for these protocols. From the results it is observed that for such situations, performance of geographic routing protocols is better than other reactive protocols. © 2013 IEEE.